Cumplimiento de la normatividad sobre estupefacientes, psicotrópicos y otras sustancias sujetas a fiscalización sanitaria de los establecimientos farmacéuticos de la región La Libertad, julio – setiembre 2015 - López Carranza, Ruth Rosali (2017)
The present report was made with the objective of determining compliance with the current regulations of the Pharmaceutical Products, Medical Devices and Medical Devices Act No. 29459 and its D.S. N ° 023-2001-SA on narcotics, psychotropics and other substances subject to sanitary inspection. For this, the quarterly balance sheets of the pharmaceutical establishments of La Libertad region were submitted to the Drug Control Area of the Functional Unit for Regulation of Drugs, Supplies and Drugs (UFREMID), which belong to the period july-september 2015. These balances were submitted until the fortnight of october, then revised and evaluated to comply with the correct filling and the attached documentation, they must comply with the DS N ° 023- 2001-SA for the presentation of the quarterly balance sheets. Lastly, the Quarterly Balance Sheet of Substances and / or Drugs of the Schedule IIA, IIIA, IIIB and IIIC of all the balance sheets presented by the pharmaceutical establishments was completed. As a result, Pharmacies with 66.67%, Pharmacies of health facilities with 53.13%, Boticas with 46.15% and Pharmacies with 40%, comply with current regulations